REVALORISING FOOD PROCESSING WASTE: CONSUMER PERCEPTION OF SEAFOOD- AND VEGETABLE-ENRICHED NOODLES - Hartono Thios; Diva Andhiny Jato; Valencia Manggala; Michael Ricky Sondak (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study examines the sensory acceptability of noodles enriched with shrimp shell powder, fish bone powder, and mustard stalk extract as part of a sustainable food waste valorization strategy. By assessing color, taste, aroma, and texture across different substitution levels, the research highlights the trade-offs between enhanced nutritional profiles and consumer acceptance. Results indicate that while lower inclusion levels maintain desirable sensory qualities, higher levels can lead to less appealing color, more pungent fishy odors, and bitter or mineral-like tastes that may limit market success. These findings underscore the need for careful formulation and advanced processing to strike a balance between functionality and palatability. The outcomes offer practical insights for food producers seeking to develop functional foods that align with the principles of a circular economy. Furthermore, this study contributes to ongoing discussions about the revalorization of seafood and agricultural by-products, especially in regions with high seafood consumption and waste generation. Future research should focus on optimizing ingredient treatment, exploring taste-masking strategies, and engaging consumers through education to increase the acceptance of novel, sustainable ingredients in staple foods.